Implementasi Kedisiplinan Peserta Didik Terhadap Budaya Religius Di Kelas VIII-5, VIII-7, VIII-8 SMPN 16 Kota Bogor - Kurnia Sari; Indry Nirma Yunizul Pesha (Ikatan Dai Indonesia, 2025)
The implementation of student discipline can make students build a nation and have a goal in success. Religious culture can improve students in understanding religious matters in daily life. The background of this study is that there are still students who have not fully complied with the rules of discipline and have not carried out religious culture as set by the school. Therefore, the focus of the problem is the implementation of discipline in grades VIII-5 (30 person), VIII-7 (35 person), VIII-8 (30 person) SMPN 16 Bogor City. This study aims to determine the implementation of student discipline towards religious culture in grades VIII-5, VIII-7, VIII-8 SMPN 16 Bogor City, Student discipline in improving religious culture VIII-8 SMPN 16 Bogor City. To find out the inhibiting and supporting factors for the implementation of students' discipline towards religious culture in grades VIII-5, VIII-7, VIII-8. Through a descriptive qualitative analysis approach, data is collected through interviews and documentation, then analyzed through the stages of reduction and drawing conclusions. The results of the study show that in general, the implementation of discipline is going quite well. The majority of students have arrived on time, dressed neatly, and participated in religious activities such as reading the Qur'an, dhuha prayers, and congregational zuhur prayers. In class VIII-5, there were 25 students who were disciplined and 5 who were not disciplined, in class VIII-7 there were 30 students who were disciplined and 5 were not disciplined, while in class VIII-8 there were 24 students who were disciplined and 6 were not disciplined. Student discipline is seen from the role of teachers in improving discipline, as well as the role of parents to students of SMPN 16 Bogor City.